Evolocumab and lipoprotein apheresis combination therapy may have synergic effects to reduce low‐density lipoprotein cholesterol levels in heterozygous familial hypercholesterolemia: A case report. Issue 4 (11th April 2018) - Zenti, M. G.; Stefanutti, C.; Sanga, V.; Altomari, A.; Fabris, A.; Dauriz, M.; Bonora, E.
Abstract : A 49 years old woman (weight 68 kg, BMI 27.3 kg/m 2 ) with heterozygous familial hypercholesterolemia (HeFH) and multiple statin intolerance with muscle aches and creatine kinase elevation, presented at the Outpatient Lipid Clinic of Verona University Hospital in May 2015. Hypercholesterolemia was firstly diagnosed during adolescence, followed in adulthood by a diagnosis of Cogan's syndrome, a rheumatologic disorder characterized by corneal and inner ear inflammation. No xanthomas, corneal arcus, or vascular bruits were detectable at physical examination. Screening for macrovascular complications did not reveal relevant damages. Ongoing medical therapy included salicylic acid, methylprednisolone, methotrexate, and protonic‐pump inhibitor. In the absence of specific lipid‐lowering therapy, plasma lipid levels at first visit were: total‐cholesterol = 522 mg/dL, LDL‐cholesterol = 434 mg/dL, HDL‐cholesterol = 84 mg/dL, triglycerides = 120 mg/dL, Lp(a) = 13 mg/dL. On December 2015, evolocumab 140 mg sc every 2 weeks was initiated. After a 24‐week treatment, the LDL‐cholesterol levels decreased by an average of 21.2% to 342 ± 22 mg/dL (mean ± SD). On May 2016, LDL‐apheresis (H.E.L.P.system) was started as add‐on therapy. Compared to the average levels obtained during the evolocumab monotherapy period, the LDL‐cholesterol was reduced by 49.4%, thus reaching an inter‐apheresis level (mean ± SD) of 173 ± 37 mg/dL. This report suggests that a combination therapy with evolocumab and lipoprotein‐apheresis may have synergic effects on circulating lipid levels. Its relevance as a highly effective treatment option for hyperlipidemia in HeFH patients warrants further investigation in larger datasets.